Q-switched cladding pumped erbium-ytterbium co-doped fiber laser with molybdenum disulfide saturable absorber - Babar, M.; Harun, Sulaiman Wadi; Yasin, Moh (Old City Publishing, 2018)
A Q-switched Erbium-Ytterbium co-doped fiber laser (EYDFL) with cladding pumping system is demonstrated by using a Molybdenum disulfide (MoS 2 ) embedded into polyvinyl alcohol (PVA) as a Saturable absorber (SA). The SA was fabricated by liquid phase exfoliation method, embedded into PVA film and integrated into a ring cladding pumped laser cavity to generate stable Q-switched laser at around 1563 nm. The laser has a multimode pump power threshold of 100 mW, a pulse repetition rate tunable within 6.4 kHz to 113.4 kHz, the maximum pulse energy of 96.67 nJ and a minimum pulse duration of 3.39 μs. The result indicates that MoS 2 nanomaterial could become a promising SA for generating Q-switching pulse train in cladding pump laser system.